PENGARUH REPUTASI UNDERWRITER DAN UMUR PERUSAHAAN, TERHADAP UNDERPRICING SAHAM PADA SAAT INITIAL PUBLIC OFFERING - Dinnul Alfian Akbar; Fernando Africano (AL-QARDH, 2019)
Underpricing is a condition where the stock price in the primary market is lower than the stock price in the secondary market. There are various factors that can affect the level of underpricing of both financial and non-financial factors. This study aims to analyze the effect of underwriter reputation and company age on underpricing.This study uses a sample of companies listed on the Indonesian Sharia Stock Index (ISSI) which conducted an initial public offering in the 2014-2018 period. The sampling technique was conducted using the purposive sampling method with predetermined criteria. Obtained a sample of 88 companies.The results showed that all variables simultaneously had a significant effect on the level of undepricing of shares. Partially the underwriter reputation variable has a significant negative effect on the level of underpricing of shares, while the firm age does not significantly influence the underpricing of shares. The magnitude of the influence of the independent variable research on underpricing shares is 32.4% while the rest is influenced by other variables outside the study